Tenggang Waktu, Tenggang Rasa, Tindakan Sebagai Perlakuan Pembiayaan Murabahah Pasca Bencana Palu, Sigi, dan Donggala - Fadel, Mochamad; Halwi, Muhammad Darma; Jurana, Jurana (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study aims to explore and find out the treatment of murabahah financing after the September 28, 2018 disaster. The natural disaster that occurred in Palu on September 28 2018 was an earthquake that occurred as a result of activities in the large zone of Palu Koro which had a magnitude of 7.4 on the Richter scale which had an impact on performance banks, mainly related to non-performing loans (NPL) resulting from the inability of the debtor. This research was conducted in the city of Palu at Bank Syariah Indonesia on the treatment of murabahah financing after the Pasigala disaster. Using a Qualitative method with an Ethnomethodology approach. Data collection methods used are observation, documentation, and interviews. The results of this study found that the treatment of murabahah financing after the Pasigala disaster at the BSI muh yamin branch was to provide a grace period: postponement of payment of debt obligations, Grace: hold deliberations for customers who have not been able to pay financing at all, and action: obligations that must repaid, but there is no credit bleaching or debt relief for disaster victims